Prognostic and Predictive Factors for Oral Squamous Cell Carcinoma: A Review (International Journal of Food and Nutritional Sciences, 2022)
The extraordinary occurrence of oral squamous cell carcinoma and its unfavourable prognosis encourage further study of variables that can affect the course of the disease. In this review paper, the authors discuss the variables that may have an impact on the prognosis and ultimately help choose which patients will receive more aggressive treatments. Three primary groups of factors associated to patients, tumours, and treatments were formed using collected, chosen, and grouped published scientific data. Aspects that are well known as well as others that are uncommon or have only hypothetical utility are examined. The prognosis is greatly influenced by the disease stage, extracapsular spread, the presence of a disease-free resection margin, and tumour thickness. The research of tumour molecular variables has drawn increased attention recently, and some of these factors have been closely connected with the outcome, indicating prospective avenues for the creation of future prognostic systems and anticancer medicines.